2023
DOI: 10.3389/fmed.2023.1200963
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive skin measurement methods and diagnostics for vitiligo: a systematic review

Abstract: Vitiligo is a multifaceted autoimmune depigmenting disorder affecting around 0.5 to 2.0% of individuals globally. Standardizing diagnosis and therapy tracking can be arduous, as numerous clinical evaluation methods are subject to interobserver variability and may not be validated. Therefore, there is a need for diagnostic tools that are objective, dependable, and preferably non-invasive.AimsThis systematic review provides a comprehensive overview of the non-invasive objective skin measurement methods that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Histopathology is the gold standard procedure for diagnosing vitiligo, but since it is invasive, it is not often accepted by patients. 14 Therefore, dermoscopy is emerging as a unique diagnostic method for vitiligo that eliminates the necessity for a skin sample. Based on the finding it can be concluded that dermatoscopy is an excellent method for diagnosing vitiligo and assessing disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology is the gold standard procedure for diagnosing vitiligo, but since it is invasive, it is not often accepted by patients. 14 Therefore, dermoscopy is emerging as a unique diagnostic method for vitiligo that eliminates the necessity for a skin sample. Based on the finding it can be concluded that dermatoscopy is an excellent method for diagnosing vitiligo and assessing disease activity.…”
Section: Discussionmentioning
confidence: 99%
“… 8-10 , 12 , 13 , 15 , 21 Although designed for objective measurements, instrumental tools are subject to operator-dependent data acquisition and interpretation, introducing subjectivity that, along with regular calibration needs, can lead to considerable intraobserver and interobserver variabilities. 22-25 Moreover, these techniques tend to focus on specific skin characteristics, such as hydration or elasticity, rather than providing an all-encompassing assessment of skin quality. Existing validated clinical scales are designed to isolate individual skin factors or specifically measure the degree of skin aging.…”
Section: Discussionmentioning
confidence: 99%
“…(4) To this day, the diagnosis of vitiligo continues to rely mainly on clinical presentation. (5) Current therapies to treat vitiligo include topical anti-inflammatory treatments, phototherapy, but also oral steroids, conventional immunosuppressants/immunomodulators, new targeted treatments such as Janus Kinase (JAK) inhibitors and surgical interventions. (6) However, these treatments are often only partially effective, cause adverse events and relapse of the disease can be seen after stopping treatment.…”
Section: Introductionmentioning
confidence: 99%

Proteomics data in vitiligo: a scoping review

Berrevoet,
Van Nieuwerburgh,
Deforce
et al. 2024
Preprint